Efektivitas Pelaksanaan Benchmarking Pendidikan Dan Pelatihan Kepemimpinan Di Badan Pengembangan Sumber Daya Manusia Daerah Provinsi Sulawesi Tengah - Bambang Sunaryo (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2019)
This research is motivated by important benchmarking into best practices in supporting the success of Level III and IV Leadership Education and Training participants so that participants are able to support and adapt organizational excellence that has best practices in organizational planning and implementation in the form of lessons, which ultimately needed as input for preparing the Change Project through innovation planning and change management. organized by the Regional Human Resources Development Agency of Central Sulawesi Province. Based on the above background, the problem solving benchmarking problem is formulated to best practice by measuring 1. Clarity of objectives to be achieved; 2. Clarity of goal completion strategies; 3. The process of analyzing and formulating conversations; 4. Planning; 5. Compilation program; 6. The availability of facilities and infrastructure; 7. Supervision and control system. This research method is qualitative descriptive combined with interviews with Leadership Training and Education Level III and IV participants in the Central Sulawesi Regional Human Resources Development Agency. The results of the study are to measure the implementation of benchmarks that have been carried out by the Regional Human Resources Development Agency of Central Sulawesi Province.